2017
DOI: 10.1021/acs.est.7b00248
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Nitrogen-Containing Organic Compounds in Humic-like Substances Emitted from Straw Residue Burning

Abstract: The molecular composition of humic-like substances (HULIS) in different aerosol samples was analyzed using an ultrahigh-resolution mass spectrometer to investigate the influence of biomass burning on ambient aerosol composition. HULIS in background aerosols were characterized with numerous molecular formulas similar to biogenic secondary organic aerosols. The abundance of nitrogen-containing organic compounds (NOC), including nitrogen-containing bases (N-bases) and nitroaromatics, increased dramatically in amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
148
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(158 citation statements)
references
References 88 publications
9
148
0
Order By: Relevance
“…the atmosphere is expected to be higher when biomass burning occurs (Wang et al, 2017). We found that in wet deposition K + /WSOC ratio showed higher level during fall in both years, even at the urban GIG site (Figure 4), indicating an enhanced biomass burning during the period .…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 72%
See 2 more Smart Citations
“…the atmosphere is expected to be higher when biomass burning occurs (Wang et al, 2017). We found that in wet deposition K + /WSOC ratio showed higher level during fall in both years, even at the urban GIG site (Figure 4), indicating an enhanced biomass burning during the period .…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 72%
“…K + is normally regarded as a tracer of biomass burning (Andreae, ; Chen et al, ; Mardi et al, ; Shi et al, ; Wang et al, ), and water‐soluble organic carbon (WSOC) is mostly derived from biomass burning and secondary formation (Ding et al, ; Weber et al, ). Therefore, the ratio of K + /WSOC in the atmosphere is expected to be higher when biomass burning occurs (Wang et al, ). We found that in wet deposition K + /WSOC ratio showed higher level during fall in both years, even at the urban GIG site (Figure ), indicating an enhanced biomass burning during the period (He et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are just some examples with higher relative intensity (RI). The RI may not accurately represent their relative concentration levels in each sample, as the MS responses of different OSs are also influenced by different carbon chain structures (Wang et al, 2017d). The OS species of low MW and short carbon chain structures (with fewer than six carbon atoms in the molecule) are less retained on the SPE cartridges due to their highly water-soluble and more hydrophilic properties Lin et al, 2012Lin et al, , 2010.…”
Section: Other Online and Offline Measurementsmentioning
confidence: 99%
“…However, one noted limitation is a lack of commercially available authentic standards. As a result, surrogate standards are often used for quantification Riva et al, 2015;, which adds uncertainty to the concentrations (Wang et al, 2017d). Recently, a few research groups quantified some OS species using synthetic authentic standards (e.g., hydroxyacetone sulfate, glycolic acid sulfate, lactic acid sulfate, methyltetrol sulfate, aromatic OSs, αand β-pinene OS, limonene OS, and limonaketone OS; Hettiyadura et al, 2017Hettiyadura et al, , 2015Olson et al, 2011;Wang et al, 2017d;Ma et al, 2014;Staudt et al, 2014), which was very important for understanding the variation and formation of OSs in ambient aerosols.…”
mentioning
confidence: 99%